Sustainable behavior change at Kansas State University: applying the Fogg Behavior Model as a community-based social marketing approach among faculty and staff - Stephens, Maggie (Kansas State University, 2014)
Communities are currently faced with the issue of integrating sustainable practices into citizen lifestyles, a problem that can be addressed through behavior changes strategies. Higher education institutions can provide a testing ground for different behavior change strategies, specifically the Fogg Behavior Model (FBM) and its application to the social structures that are important in community-based social marketing (CBSM). This research proposes to examine FBM among Kansas State University faculty and staff as a viable CBSM approach for sustainable behavior change. A targeted behavior and trigger for the targeted behavior were selected. The trigger was implemented among select university departments with both pre- and post-experiment surveys distributed to assess trigger effectiveness and limiting factors to ability and motivation. The research showed an increase to the targeted behavior due to trigger implementation and described ability and motivation limiting factors within those select departments. With further investigation into these limiting factors and a widespread trigger effectiveness study, FBM could serve as an effective model that addresses social behavior change within a CBSM framework. FBM’s potential success in a university setting bodes well for its success in communities and a community-based social marketing approach to create sustainable behavior change.
Keywords: Sustainable behavior change; Fogg behavior model; Community-based social marketing; Sustainability (0640)